2016
DOI: 10.1159/000445609
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223-3p as a Novel MicroRNA Regulator of Expression of Voltage-Gated K+ Channel Kv4.2 in Acute Myocardial Infarction

Abstract: Background/Aims: Acute myocardial infarction (AMI) is a devastating cardiovascular disease with a high rate of morbidity and mortality, partly due to enhanced arrhythmogenicity. MicroRNAs (miRNAs) have been shown to participate in the regulation of cardiac ion channels and the associated arrhythmias. The purpose of this study was to test our hypothesis that miR-223-3p contributes to the electrical disorders in AMI via modulating KCND2, the gene encoding voltage-gated channel Kv4.2 that carries transient outwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 51 publications
2
52
0
Order By: Relevance
“…Both strands (5p and 3p) of miR-223 were remarkably dysregulated in mouse hearts subjected to I/R, in which they cooperatively suppressed necroptosis [35]. Liu et al reported that miR-223 was upregulated in a rat model of AMI and that its overexpression can promote arrhythmias; thus, miR-223 may be a new target in the treatment of ischemic arrhythmias [36]. The abovementioned studies elucidated the roles of miR-223 in various cardiac diseases, focusing specifically on the roles of miR-223 in various metabolic, hypertrophic and necrotic processes; however, they did not investigate whether or not miR-223 impacts cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both strands (5p and 3p) of miR-223 were remarkably dysregulated in mouse hearts subjected to I/R, in which they cooperatively suppressed necroptosis [35]. Liu et al reported that miR-223 was upregulated in a rat model of AMI and that its overexpression can promote arrhythmias; thus, miR-223 may be a new target in the treatment of ischemic arrhythmias [36]. The abovementioned studies elucidated the roles of miR-223 in various cardiac diseases, focusing specifically on the roles of miR-223 in various metabolic, hypertrophic and necrotic processes; however, they did not investigate whether or not miR-223 impacts cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…4A-C ). Two other microRNAs, miR-223-3p and miR-301a-3p, were shown to regulate Kv4.2 in the heart (Panguluri et al, 2013, Liu et al, 2016), but their function in neurons and during seizures is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Zhi et al showed that miR-223 was shown to inhibit bladder cancer cell migration and invasion by downregulating its target ZEB1 [25]. In addition, miR-223 was shown to be a potential target for the treatment of ischemic arrhythmias, as miR-223 repressed the expression of the voltage-gated K+ channel Kv4.2 [26]. miR-223 suppresses cardiomyocyte hypertrophy by modulating the expression of its target TNNI3K, a troponin interacting kinase [27].…”
Section: Discussionmentioning
confidence: 99%